2019
DOI: 10.1007/s00192-019-04186-3
|View full text |Cite
|
Sign up to set email alerts
|

Posterior tibial nerve stimulation for overactive bladder—techniques and efficacy

Abstract: The ideal treatment for overactive bladder is still elusive. In those where medication fails to improve symptoms options include invasive treatments such as botulinum toxin-A, sacral neural stimulation or posterior tibial nerve stimulation. Scientific professional society guidelines advise percutaneous posterior tibial nerve stimulation as a third line treatment option only after multidisciplinary team review as well as failure of both conservative and pharmacological management. The aim of this article is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 35 publications
2
52
0
1
Order By: Relevance
“…The PTN is a distal branch of the sciatic nerve that originates in the pelvis (L5–S3 spinal roots) and descends towards the lower extremities. [ 26 ] Stimulation of the PTN delivers retrograde neuromodulation to the sacral nerve plexus that controls the bladder function. TNS is a form of neuromodulation involving the use of electrical impulses to address urinary symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PTN is a distal branch of the sciatic nerve that originates in the pelvis (L5–S3 spinal roots) and descends towards the lower extremities. [ 26 ] Stimulation of the PTN delivers retrograde neuromodulation to the sacral nerve plexus that controls the bladder function. TNS is a form of neuromodulation involving the use of electrical impulses to address urinary symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…TNS is a form of neuromodulation involving the use of electrical impulses to address urinary symptoms. [ 26 ] Two routines were usually applied during TNS, including transcutaneous and percutaneous approaches. Two RCTs comparing PTNS with sham stimulation have proved PTNS effective and acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior tibial nerve stimulation involves the use of electrical impulses and is a form of neuromodulation employed to improve urinary symptoms 37 . This can be in the form of percutaneous tibial nerve stimulation (PTNS), which uses a needle, and transcutaneous tibial nerve stimulation (TTNS), which uses pads.…”
Section: Neuromodulationmentioning
confidence: 99%
“…An external control unit is worn around the ankle to activate the electrodes. This unit is worn six times a week for 30 minutes to activate treatment 37 , 38 . A study of 15 patients (13 female) showed a significant improvement in frequency, urgency, and urgency incontinence episodes at 3 months 38 .…”
Section: Neuromodulationmentioning
confidence: 99%
“…In the past 5 years, nearly 60 centers in China have carried out SNM clinical studies, and there are also several clinical articles published in China that report the efficacy and prognosis of SNM (Chen et al, 2014;Zhang et al, 2017). Researchers are also exploring other pelvic floor and peripheral nerves as new regulatory targets to achieve better efficacy and reduce associated complications, such as the pudendal nerve (Marinkovic et al, 2015) and the tibial nerve (Bhide et al, 2020). The pudendal nerve is one of the main nerves that stimulates pelvic floor muscles, external urethral meatus, the anal sphincter, and pelvic organs, and it is composed of nerve fibers emanating from S2 to S4 nerve roots.…”
Section: Introductionmentioning
confidence: 99%